"I Was Not Sick and I Didn't Need to Recover": Methadone Maintenance Treatment (MMT) as a Refuge from Criminalization. (28th January 2018) - Frank, David
ABSTRACT: Background : Methadone Maintenance Treatment (MMT) in the United States (U.S.) has been undergoing a shift towards conceptualizing the program as recovery-based treatment. Although recovery is seen by some as a means to restore MMT to its rightful position as a medically-based treatment for addiction, it may not represent the experiences, or meet the needs of people who use drugs (PWUD), many of whom who use the program as a pragmatic means of reducing harms associated with criminalization. Objectives : To examine alternative constructions of MMT in order to produce a richer, more contextualized picture of the program and the reasons PWUD employ its services. Methods : This paper uses semi-structured interviews with 23 people on MMT (either currently or within the previous two years). Results : Most participants linked their use of MMT to the structural-legal context of prohibition/criminalization rather than through the narrative of the recovery model. Responses suggested the recovery model functions in part to obscure the role of criminalization in the harms PWUD experience in favor of a model based on individual pathology. Conclusions/Importance : In contrast to the recovery model, MMT cannot be understood outside of the structural context of criminalization and the War on Drugs which shape illegal drug use as a difficult and dangerous activity, and consequently position MMT as a way to moderate or escape from those harms.